ANALISIS TINGKAT KESEHATAN KOPERASI KREDIT “KOSAYU” PERIODE 2014-2016 BERDASARKAN PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTERIAN KOPERASI DAN USAHA KECIL DAN MENENGAH REPUBLIK INDONESIA NOMOR: 06/PER/DEP.6/IV/2016 - Putri Sekti Purnama Sari (Jurnal Ilmiah Mahasiswa FEB, 2016)
The study tries to determine the health level of “Kosayu” Credit Cooperatives during the period of 2014-2016 viewed from its financial and management aspects. This descriptive quantitative research applies a case-study towards “Kosayu” Credit Cooperatives. The data analysis are derived from the Regulation of the Deputy of Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia, Number: 06/Per/ Dep.6/IV/2016 concerning the Guidelines for Health Assessment of the Savings and Loans Cooperatives and the Savings and Loans Unit, which covers seven aspects: capital, productive asset quality, management, efficiency, liquidity, independence and growth, and management.The results of the study show that the health level of “Kosayu” Credit Cooperatives in 2014 was under the category of "Healthy Enough" with the score 69.85, in 2015 "Healthy Enough" with the score 71.35, and in 2016 also "Healthy Enough" with the score 68.90. Although not reaching the maximum score yet, out of the seven aspects assessed, the capital, quality of productive assets, and management aspects achieve the best performance. This is evidenced by the achievement of the maximum score which is higher than other aspects; whereas, the aspects of efficiency, liquidity, awareness and growth, and identity of cooperatives are categorized less good as proven by the number of achievement score which is less than the maximum one.Keywords: Health Level of Cooperative, Cooperative Savings and Loans, Regulation of the Deputy of Supervision, Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 06/Per/Dep.6/IV/2016.